Organizational Strategy and Employee Productivity in Oil and Gas Industry: The Case of the United Arab Emirates - Al-Ansari, Haima Ali Al-Mulla (2013)
Employee productivity influences the success and growth of a firm tremendously. The oil and gas industry in Emirate of Abu Dhabi is a significant contributor towards the economic growth of the country. Owing to the advent of globalization, there is an increasing demand for improved productivity and increased efficiency from employees. To enable this, employers have to adopt organizational strategies, aligned at promoting their employees to work effectively, and efficiently. The prime focus of this research is to understand how organizations can increase employee productivity in the oil and gas industry in Emirate of Abu Dhabi, by making use of suitable organizational strategies. The influence of an organizations strategic alignment on employee productivity will be explored. The influence of a firms’ strategic alignment on employee engagement, strategic management, employee empowerment, line of sight, vision alignment, employee motivation will help in assessing the influence of the identified factors on employee productivity. To gather information relevant to the research, and to understand the views of senior managers, and leaders in Abu Dhabi oil and gas industry in depth, survey has been conducted using survey questionnaire. The questionnaire was designed to contain close-ended questions that measure the extent to which the identified factors influence employee productivity. In addition, to enhance the research validity, the variables have also been discussed in depth in the literature review chapter. To develop its reliability, results of the research generated from SPSS statistical package have been used. Also to improve the clarity of research graphs and tables are used to represent the results. Data was gathered from 200 respondents, working with various firms in the oil and gas industry having a good experience in leading and managing teams at their place of work. The hypotheses were tested using linear regression analysis, and it has been found that, employee knowledge about firm, employee engagement, and organizational strategic alignment are largely influence employee productivity. Vision alignment or line of sight, and employee motivation have a moderate influence of employee productivity.